Improvising 5-HT7R homology model for design of high affinity ligands: model validation with docking, embrace minimization, MM-GBSA, and molecular dynamic simulations. Issue 10 (27th July 2018) - Jha, Preeti; Chaturvedi, Shubhra; Swastika,; Pal, Sunil; Jain, Nidhi; Mishra, Anil K.
Abstract : The subtype, 5-HT7 R has been implicated in neurological disorders and presents itself as a promising target for antidepressant drugs. Design of targeted selective ligands, require a sound knowledge of 3D-receptor structure. In absence of receptor structure, structure-based design of targeted ligands relies on generation of 5-HT7 R homology model. In this study, the impact of template choice, alignment, and model building methods on the homology model of 5-HT7 R is addressed. The compactness and model quality due to the presence of cholesterol (lipidic receptor) have also been observed. The results suggest good stereochemical quality of the final model. Ramachandran Plot Analysis indicated more than 97.5% amino acid residues in the favorable region. The overall quality factor was 91.8% using ERRAT. The Z-score for backbone confirmation and packing quality were −1.248 and −1.427, respectively, using WHATCHECK. The RMS Z-score for side chain planarity was .711. Other validation results for the final model include binding site analysis in which Asp162, Val163, Phe343, Phe344, Arg350, Arg367, and Leu370 conserved residues were found in the active site, correlation coefficient of .82 in ligand-based screening and .85 in embrace minimization. Further, the model showed good correlation for agonist and antagonist in docking ( ≈ .76, ≈ .82), embrace minimization ( ≈ .73, ≈ .72), and MM-GBSA ( ≈ .69, ≈ .75) studies. The model was subjected to Molecular Dynamics (MD) simulation of 20 ns both in ligand-free and ligand-bound receptor (agonist and antagonist) system in order to assess its stability.